Foreign enterprises in mexico - Klaus Matthies (Intereconomics, 1975)
The uses and drawbacks of foreign capital and multinational enterprises have been discussed more thoroughly in the past few years also in Mexico. The Third World Trade Conference of 1972 (UNCTAD III), at which President Echeverría came forward with proposals designed to involve foreign enterprises in the development process, and the introduction of two laws dealing with investment and technology have stimulated this debate.
Keywords: 330; Multinational Corporations